Facilitating credentialing and engagement of international physician-migrants during the COVID-19 crisis and beyond - Tiffany Leung; Ewelina Biskup; Dawn DeWitt (James Cook University, 2020)
Context: Physicians who migrate globally face a daunting series of time-consuming, labor- and resource-intensive procedures to prove their clinical competency before being allowed to practice medicine in a new country. Issues: In this commentary, we describe licensing barriers faced by physician-migrants based on the authors' experiences, and reflect also on rapidly implemented measures to address COVID-19 pandemic related workforce shortages. We offer recommendations for potential reductions in bureaucratic regulatory barriers that prohibit mobilization of international medical graduate talent. Lessons learned: Licensing boards and authorities should strive for standardized, competency-based basic professional recognition. Professional medical societies are well-positioned to guide such competency-based recognition as a more organized, international collaborative effort across specialties. The COVID-19 pandemic facilitated cross-state and international licensing in some regions, highlighting a key opportunity: streamlining professional recognition requirements is achievable.